A new species of the genus Phytocoris (Hemiptera: Heteroptera: Miridae: Mirinae) from western Iran - Hosseini, Reza; Mohammadi, Saadi (Zootaxa, 2018)
A new species, Phytocoris (Eckerleinius) hawramanicum sp. nov is described from Iran. A revised dichotomous key to the species of subgenus Eckerleinius Wagner known in Iran and adjacent regions, illustrations of male genitalia and male habitus photographs of this new taxon are provided. Diagnosis of the new species is based on a comparison with other congeneric found from Iran and adjacent countries. The type specimens were deposited in the insect collection of the University of Guilan, Rasht, Iran.